Permainan Lompat Kodok Mempengaruhi Hasil Belajar Matematika Siswa Kelas V di SDN 51 Kota Bengkulu - Elfitria Rosa; Victoria Karjiyati; Hasnawati Hasnawati (JURIDIKDAS, 2019)
This research is a quantitative research. The research design used was Quasi Experimental Design with design type The Matching Only Pretest-Posttest Control Group Design, where the test was done twice before and after giving treatment (treatmen) in the sample class. The sample in this research is the students of class V in SD N 51 Kota Bengkulu, which consist of VA class as experiment class and VB class as control class. The research instrument used is a multiple choice test which is given through the pretest before the learning takes place and posttest after the learning takes place. Data of this research are analyzed by using descriptive analysis and inferential analysis that is t-test. The result of t-test with t count is 2.38 and ttable is 2.02. So the value of t arithmetic obtained greater than the value of t table, the conclusion of this study that there is the influence of the frog jumping game on the learning outcomes of cognitive aspects in the learning of Mathematics students of class V in SD N 51 Kota Bengkulu.